Prospects of electric-energy cooperation between Russia and northeast Asian countries - Podkoval’nikov, S. V.; Savel’ev, V. A.; Chudinova, L. Yu (Studies on Russian economic development, 2015)
The article shows trends in the development of interstate electrical connections and interconnections around the world and potential energy-economic effects of their creation. The current situation and problems of the functioning of the electric-power industry in northeast Asian countries, including eastern regions of Russia, China, Japan, the Republic of Korea, Mongolia, and the Democratic People’s Republic of Korea, and their potential role in formation of interstate power interconnection in the region has been analyzed. The potential directions and projects of transboundary power transmission between national and local electric energy systems of these countries have been shown. The role of renewable power sources (water, wind, and solar energy) in the development of interstate electrical connections and interconnections, including the Asian Super Grid interconnection, is analyzed.